ANALYSIS OF USER SATISFACTION LEVEL OF JAMSOSTEK MOBILE APPLICATION IN ACEH USING END USER COMPUTING SATISFACTION - Nurdiana, Siti; Irmalis, Amsal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Technological sophistication that continues to develop has given birth to several new innovations to make every activity that is usually carried out more effective and instantaneous, such as one of the innovations from the latest application of the BPJS Employment public body, namely Jamsostek Mobile (JMO). User satisfaction is very important to improve the development of the JMO application system, therefore the author has a goal in measuring the level of satisfaction of JMO application users using the EUCS (End User Computing Satisfaction) through the variables of content, accuracy, format, user convenience and timeliness. This research data uses quantitative methods through random sampling technique by obtaining primary data from the distribution of online questionnaires to every JMO user in Aceh. In this study there were 107 respondents. Data analysis was carried out by testing validity, reliability testing, classical assumption test, R test, F test and hypothesis testing. The results of this research data indicate that content and format significantly affect user satisfaction with a significant number of content 0.005 < 0.05 and format 0.035 < 0.05. Then other variables such as accuracy, ease of use and timeliness do not affect user satisfaction with significant figures greater than 0.05 and t count less than t table.